Pure Laparoscopic Radical Cystectomy with Ileal Conduit: A Single Surgeon's Mid-Term Outcomes - Park, Bumsoo (Yonsei University College of Medicine, 2013)
PURPOSE: The use of laparoscopic radical cystectomy (LRC) for muscle-invasive bladder cancer is not yet widespread because of the technical difficulties of the procedure and the lengthy operating time. In this study, we report a single surgeon's experience with LRC. MATERIALS AND METHODS: Thirty patients (25 men and 5 women) with bladder cancer underwent LRC and ileal conduit by a single surgeon between November 2007 and May 2011. An extracorporeal urinary diversion was performed through 5-6 cm midline incision for specimen extraction. RESULTS: The median operating time and estimated blood loss were 527.5 minutes and 275 mL, respectively. There was no conversion to open surgery. The median time to oral intake and postoperative hospital stay were 5 days and 12 days, respectively. The rates of immediate, early postoperative and late postoperative complication were 3.3%, 20% and 20%, respectively. With 16 months of median follow-up, the overall and recurrence-free survival rates were 70% and 56.7%, respectively. CONCLUSION: LRC is feasible for the management of invasive bladder cancer and, with appropriate patient selection, can be a good alternative to open or robot-assisted radical cystectomy in the era of robot-assisted surgery.